The Dilemma of “Good Practices” in Armenian Higher Education - Karakhanyan, Susanna; Khachatryan, Robert (International Higher Education, 2023)
Inconsistent and incoherent approaches to policy reforms have thwarted Armenia’s vision of establishing a democratic and competitive higher education system based on “good practices” from Western systems. Attempts at reforms have demonstrated a questionable commitment to meaningful change of the existing system, which is still heavily influenced by Soviet legacy. Armenia’s integration into the European Higher Education Area (EHEA) has turned out to be delusional, resulting in the decline of relevance and therefore quality.